Social acceptance of distributed energy systems in Swiss, German, and Austrian energy transitions. (August 2019) - Seidl, R.; von Wirth, T.; Krütli, P.
Abstract: Distributed energy systems (DESs) on a local scale constitute a promising niche to leverage renewable energy provision. These DESs (e.g., micro-cogeneration, multi-energy hubs) integrate renewable sources, combined heat and power production, various methods of energy conversion and storage, and active demand-side management. Since the broader uptake of such systems is still at an early stage, research about the adoption potentials of DESs in existing neighborhood contexts is scarce. Given their potential to contribute to energy transitions, it is relevant to gain a better understanding of the conditions under which these systems are diffused. Based on a quantitative study, we investigated the perceived responsibilities and the intended technology uptake of DESs among different societal groups in Switzerland, Germany, and Austria. We analyzed a sample of 2104 survey participants who were exposed to ranking tasks and a framing experiment and were asked questions about both opportunities and challenges in implementing DESs. Our results show an openness to engage with DESs; on average, the opportunities in applying DESs are rated higher than the challenges. However, in all three countries, the participants place the responsibility for the energy system transitions on the national government and large energy supply utilities. Municipalities and households are not yet considered relevant innovators. Moreover, the support of DESs is found to be independent from framing the DES implementation in relation to different scales of rationale (global climate change, national energy independence, or local autarky). Our findings illustrate not only the agents' attitudes toward DESs but also the structural path dependencies involving the implementation of distributed energy technologies. Our study implies the need to address the willingness to invest in new distributed energy infrastructures at the household level in the future. We discuss the necessity of identifying barriers to and drivers of technology applications ex-ante.